A clinico-immunological study of ulcerative colitis and ulcerative proctitis. Issue 1 (January 1971) - Smith, Anne Hardy; Macphee, Ian W.
Abstract : Fifteen patients with ulcerative colitis and 11 patients with ulcerative proctitis have been observed and studied for periods ranging from one to 15 years. It is suggested that the clinical course of the two disorders is quite distinct. Further, while the serum immunoglobulins were within normal limits in ulcerative proctitis, significant increases in the serum α2 -, β-, and γ-globulins and in the IgA and IgG concentrations were found in ulcerative colitis. Despite total colectomy for ulcerative colitis, the serum IgG and IgA concentration remained high and even after subsequent rectal resection the relative IgA concentration continued to increase. The significance of these findings is discussed.